Language on display : writers, fiction and linguistic culture in post-Soviet Russia - Lunde, Ingunn, 1969- (Russian language and society., 2018)
Post-Soviet Russia was a period of linguistic liberalisation, instability and change with varied attempts to regulate and legislate language usage. This book looks at how these debates featured in literature and illustrates the discussion through six interpretive readings of post-Soviet Russian prose.